The war on warriors : behind the betrayal of the men who keep us free - Hegseth, Pete (Fox News Books, 2024)
"Pete Hegseth joined the Army to fight extremists. Then that same Army called him one. The military Pete joined twenty years ago was fiercely focused on lethality, competency, and color blindness. Today our brass are following the rest of our country off the cliff of cultural chaos and weakness. Americans with common sense are fighting this on many fronts, but if we can't save the meritocracy of our military, we're definitely going to lose everywhere else. The War on Warriors uncovers the deep roots of our dysfunction--a society that has forgotten the men who take risks, cut through red tape, and get their hands dirty. The only kind of men prepared to face the dangers that the Left pretends don't exist. Unlike issues of education or taxes or crime, this problem doesn't have a zip code solution. We can't move away from it. We can't avoid it. We have only one Pentagon. Either we take it back or surrender it altogether. Combining his own war experiences, tales of outrage, and an incisive look at how the chain of command got so kinked, this book is the key to saving our warriors--and winning future wars. The War on Warriors must be won by the good guys, because when the shooting really starts, they're the only ones who can save us"--